1988
DOI: 10.1002/hep.1840080207
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin levels measured by a chromogenic assay in portal, hepatic and peripheral venous blood in patients with cirrhosis

Abstract: Endotoxin concentrations were measured in the portal, hepatic and peripheral venous blood of two groups of patients with cirrhosis using a limulus-based chromogenic assay. The high sensitivity of chromogenic detection allowed measurement of endotoxin as low as 10 to 15 pg per ml, an order of magnitude greater than previously possible by gelation studies. Group 1 consisted of 56 patients with cirrhosis undergoing angiographic evaluation. In this group, there was wide variability in hepatic venous concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
214
2
5

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(232 citation statements)
references
References 35 publications
11
214
2
5
Order By: Relevance
“…35 However, the difficulties with the measurement of endotoxin are reflected in the wide range of values in the literature and make this an unreliable indicator on which to base further management. 33,34 Our data do support the notion that endotoxin may be the putative humoral factor in patients' plasma responsible for the activation of neutrophils by showing that endotoxin increased the resting burst in healthy neutrophils while reducing phagocytosis in neutrophils from patients with alcoholic cirrhosis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…35 However, the difficulties with the measurement of endotoxin are reflected in the wide range of values in the literature and make this an unreliable indicator on which to base further management. 33,34 Our data do support the notion that endotoxin may be the putative humoral factor in patients' plasma responsible for the activation of neutrophils by showing that endotoxin increased the resting burst in healthy neutrophils while reducing phagocytosis in neutrophils from patients with alcoholic cirrhosis.…”
Section: Discussionsupporting
confidence: 75%
“…Endotoxin not only is a priming agent 6 but has been reported to fully activate neutrophils 12,13 by up-regulating the NADPH oxidase assembly. 32 The highest levels of endotoxin reported in patients with liver disease are found in portal venous blood, 33,34 highlighting the importance of the bowel and altered gut permeability as a possible source of endotoxin. 35 However, the difficulties with the measurement of endotoxin are reflected in the wide range of values in the literature and make this an unreliable indicator on which to base further management.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxins are complex, amphiphilic macromolecules of up to 1000 kD in molecular weight, making free glomerular filtration unlikely, supported by research showing endotoxin is not present in sterile urine (29). The levels seen in patients receiving dialysis are extremely high, comparable with those reported in severe liver disease (30), gut irradiation (31), and severe decompensated heart failure (4). Significant heart failure (New York Heart Association class III to IV) was an exclusion criterion and, in the HD patients, endotoxin levels did not correlate with markers of volume overload.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, as demonstrated by several studies over the last decade macrophage-and platelet-derived endocannabinoids contribute to the hypotension associated with hemorrhagic (Wagner et al, 1997), endotoxic (Varga et al, 1998;Liu et al, 2003;Bátkai et al, 2004;Wang et al, 2001) and cardiogenic shock (Wagner et al, 2001a. Furthermore, a similar mechanism seems to be involved in the vasodilated state associated with advanced liver cirrhosis (Bátkai et al, 2001;Ros et al, 2002), which is possibly secondary to the endotoxemia frequently found in patients with latestage cirrhosis (Lumsden et al, 1988). Importantly, in all of the above-mentioned pathological conditions the hypotension could be reversed or inhibited by the CB 1 antagonist SR141716.…”
Section: Role Of the Endocannabinergic System In The Hypotension Assomentioning
confidence: 95%